The role of digital communication in patient–clinician communication for NHS providers of specialist clinical services for young people [the Long-term conditions Young people Networked Communication (LYNC) study]: a mixed-methods study - Frances E Griffiths; Xavier Armoiry; Helen Atherton; Carol Bryce; Abigail Buckle; Jonathan AK Cave; Rachel Court; Kathryn Hamilton; Thandiwe R Dliwayo; Melina Dritsaki; Patrick Elder; Vera Forjaz; et al. (Health Services and Delivery Research, 2018)
Background: Young people (aged 16–24 years) with long-term health conditions tend to disengage from health services, resulting in poor health outcomes. They are prolific users of digital communications. Innovative UK NHS clinicians use digital communication with these young people. The NHS plans to use digital communication with patients more widely. Objectives: To explore how health-care engagement can be improved using digital clinical communication (DCC); understand effects, impacts, costs and necessary safeguards; and provide critical analysis of its use, monitoring and evaluation. Design: Observational mixed-methods case studies; systematic scoping literature reviews; assessment of patient-reported outcome measures (PROMs); public and patient involvement; and consensus development through focus groups. Setting: Twenty NHS specialist clinical teams from across England and Wales, providing care for 13 different long-term physical or mental health conditions. Participants: One hundred and sixty-five young people aged 16–24 years living with a long-term health condition; 13 parents; 173 clinical team members; and 16 information governance specialists. Interventions: Clinical teams and young people variously used mobile phone calls, text messages, e-mail and voice over internet protocol. Main outcome measures: Empirical work – thematic and ethical analysis of qualitative data; annual direct costs; did not attend, accident and emergency attendance and hospital admission rates plus clinic-specific clinical outcomes. Scoping reviews–patient, health professional and service delivery outcomes and technical problems. PROMs: scale validity, relevance and credibility. Data sources: Observation, interview, structured survey, routinely collected data, focus groups and peer-reviewed publications. Results: Digital communication enables access for young people to the right clinician when it makes a difference for managing their health condition. This is valued as additional to traditional clinic appointments. This access challenges the nature and boundaries of therapeutic relationships, but can improve them, increase patient empowerment and enhance activation. Risks include increased dependence on clinicians, inadvertent disclosure of confidential information and communication failures, but clinicians and young people mitigate these risks. Workload increases and the main cost is staff time. Clinical teams had not evaluated the impact of their intervention and analysis of routinely collected data did not identify any impact. There are no currently used generic outcome measures, but the Patient Activation Measure and the Physicians’ Humanistic Behaviours Questionnaire are promising. Scoping reviews suggest DCC is acceptable to young people, but with no clear evidence of benefit except for mental health. Limitations: Qualitative data were mostly from clinician enthusiasts. No interviews were achieved with young people who do not attend clinics. Clinicians struggled to estimate workload. Only eight full sets of routine data were available. Conclusions: Timely DCC is perceived as making a difference to health care and health outcomes for young people with long-term conditions, but this is not supported by evidence that measures health outcomes. Such communication is challenging and costly to provide, but valued by young people. Future work: Future development should distinguish digital communication replacing traditional clinic appointments and additional timely communication. Evaluation is needed that uses relevant generic outcomes. Study registration: Two of the reviews in this study are registered as PROSPERO CRD42016035467 and CRD42016038792. Funding: The National Institute for Health Research Health Services and Delivery Research programme.